Employee Performance from perspective Workload and Work Environmental - Rachmat Kurniawan, Yudi (Siber International Journal of Digital Business (SIJDB), 2025)
The purpose of this study is to determine and analyze: (1) Workload (2) Work Environment; (3) Employee performance; and (4) The Influence of Workload and Work Environment on Employee Performance at XYZ Company in Bandung City, both simultaneously and partially. The research method used in this study is descriptive survey and explanatory survey, the unit of analysis in this study is employees at XYZ Company in Bandung City with a sample of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was obtained that the Workload experienced by Employees at XYZ Company in Bandung City is good, the Work Environment at XYZ Company in Bandung City can generally be said to be good, Employee Performance at XYZ Company in Bandung City is currently considered good. Workload and Work Environment affect Employee Performance at XYZ Company in Bandung City simultaneously and partially. However, partially Workload predominantly affects Employee Performance rather than Work Environment. Because Workload more dominantly affects Performance, it becomes the first priority in improving Performance. Therefore, employees at XYZ Company in Bandung are advised to improve their working conditions and atmosphere, so that they are able to work more professionally.